Liquidity, Managerial Ownership and Price to Book Value on Stock Prices in Transportation Sub Sector Companies - I Wayan Gede Agus Putra KARANG; Ida Idam Manik SASTRI; Putu Gede Wisnu Permana KAWISANA (Journal of Governance, Taxation and Auditing, 2022)
Stock prices in transportation sub-sector companies are still fluctuating and tend to decline. This indicates that investors' confidence in companies in transportation sub-sector companies is decreasing due to declining stock prices which are assumed to decrease the company's performance, so this causes the market response and investors are not optimistic in investing their capital in companies in transportation sub-sector companies. This study aims to empirically examine the effect of liquidity, managerial ownership and price to book value (PBV) on stock prices in transportation sub-sector companies in 2018-2020. The research method used purposive sampling. This type of data uses quantitative data and secondary data sources. Methods of data collection using the study of documentation. The data analysis technique used multiple linear regression test. The results show that liquidity has no significant effect on stock prices in transportation sub-sector companies in 2018-2020. Managerial ownership and price to book value (PBV) have a positive and significant effect on stock prices in transportation sub-sector companies in 2018-2020.